First report of Anisakis spp. in freshwater fish in Huacho, Peru - Airahuacho Bautista, Felix Esteban (2020)
The objective of this study was to establish the presence of Anisakis spp in freshwater fish in the El Paraíso wetland, in Huacho, Peru, due to massive parasitism observed in previous studies of identification of aquatic communities. The parasites were sampled in three common species in the wetland. Results showed 90, 75 and 66% of fish Dormitator latifrons, Mugil cephalus and Lebiasina bimaculata were infested with Anisakis parasites in larval stage L3, respectively. In addition, 50 and 25% of D. latifrons and M. cephalus, respectively, presented larvae of this parasite in the liver and visceral cavity. On macroscopic inspection, the Anisakis spp larva is observed spirally attached to the liver or disseminated in the intestines. Microscope images show the penetration tooth and the mucron, specific characteristics in the identification of Anisakis larvae. The present study is a first report of the presence of Anisakis spp in freshwater species.